The Analysis of Income per Capita Convergence on ASEAN Plus Three (APT) Countries - Any Fatiwetunusa; Syamsurijal Syamsurijal; Sa'adah Yuliana (Faculty of Economics, Universitas Sriwijaya, 2017)
The main objective of this study is to test the convergence of income per capita in APT countries through three models: absolute convergence, conditional convergence and sigma convergence. Regression analysis of panel data from 13 APT countries during the period of 2001-2014 is used to analysed to study problem. In absolute convergence model, the growth of real GDP per capita and initial real GDP are used as the variables, meanwhile, 8 variables such as the growth of real GPD per capita, initial real GDP per capita, labor force ratio, value added in agricultural sector, value added in industrial sector, terms of trade, foreign direct investment and internet users ratio are analyzed in conditional convergence model. According to the Solow model, the economies of the countries will converge in which the growth of income per capita of developing countries will be higher than those of developed countries. The economies will be convergent if the countries tend to move to a similar steady state resulting in smaller gap between the countries. Based on the results of absolute convergence and conditional convergence models, APT countries is converging with the rate of 2% and 2.2%. This is consistent with the results of sigma convergence model that shows a declining trend in the dispersion of real GDP per capita in APT regions. The growth of real GDP per capita is influenced by initial GDP per capita, labor force ratio, value added in agricultural sector, value added in industrial sector, terms of trade, foreign direct investment and internet users ratio. Developed countries such as Singapore, Brunei Darussalam and South Korea experience the impact of high real GDP per capita growth. On the contrary, Indonesia, Laos, Vietnam and The Phillipines undergo the impact of low GDP per capita growth.